Fatty acid synthase mediates EGFR palmitoylation in EGFR mutated non‐small cell lung cancer. Issue 3 (15th February 2018) - Ali, Azhar; Levantini, Elena; Teo, Jun Ting; Goggi, Julian; Clohessy, John G; Wu, Chan Shuo; Chen, Leilei; Yang, Henry; Krishnan, Indira; Kocher, Olivier; Zhang, Junyan; Soo, Ross A; et al.
Abstract: Metabolic reprogramming is widely known as a hallmark of cancer cells to allow adaptation of cells to sustain survival signals. In this report, we describe a novel oncogenic signaling pathway exclusively acting in mutated epidermal growth factor receptor (EGFR) non‐small cell lung cancer (NSCLC) with acquired tyrosine kinase inhibitor (TKI) resistance. Mutated EGFR mediates TKI resistance through regulation of the fatty acid synthase (FASN), which produces 16‐C saturated fatty acid palmitate. Our work shows that the persistent signaling by mutated EGFR in TKI‐resistant tumor cells relies on EGFR palmitoylation and can be targeted by Orlistat, an FDA‐approved anti‐obesity drug. Inhibition of FASN with Orlistat induces EGFR ubiquitination and abrogates EGFR mutant signaling, and reduces tumor growths both in culture systems and in vivo . Together, our data provide compelling evidence on the functional interrelationship between mutated EGFR and FASN and that the fatty acid metabolism pathway is a candidate target for acquired TKI‐resistant EGFR mutant NSCLC patients. Synopsis: In EGFR mutated Non‐Small Cell Lung Carcinoma with acquired Tyrosine Kinase Inhibitors resistance, FASN mediates EGFR palmitoylation and supports tumor growth. With limited effective therapeutics, these data show that FASN is a candidate target for acquired TKI‐resistant EGFR mutant NSCLC. Identification of a positive feedback loop involving mutated EGFR and FASN in EGFR mutated NSCLC with acquired TKI resistance. FASN‐mediated EGFR palmitoylaton is crucial for survival of NSCLC cells, and influences its translocation to the nucleus. FASN inhibition suppresses tumor growth in both cell culture systems and in vivo models, highlighting its potential as a target for therapeutic intervention. Abstract : In EGFR mutated Non‐Small Cell Lung Carcinoma with acquired Tyrosine Kinase Inhibitors resistance, FASN mediates EGFR palmitoylation and supports tumor growth. With limited effective therapeutics, these data show that FASN is a candidate target for acquired TKI‐resistant EGFR mutant NSCLC.